2018
DOI: 10.1103/physrevlett.121.258001
|View full text |Cite
|
Sign up to set email alerts
|

Revealing a Vacancy Analog of the Crowdion Interstitial in Simple Cubic Crystals

Abstract: Vacancies in simple cubic crystals of hard cubes are known to delocalize over one-dimensional chains of several lattice sites. Here, we use computer simulations to examine the structure and dynamics of vacancies in simple cubic crystals formed by hard cubes, right rhombic prisms (slanted cubes), truncated cubes, and particles interacting via a soft isotropic pair potential. We show that these vacancies form a vacancy analog of the crowdion interstitial, generating a strain field which follows a soliton solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…crowdions-voidions pair). 37,38 Second, the sensitivity to the atomic planes periodicity d revealed an anisotropic 3.4% expansion of the CsPbBr3 structure in going from N=13 nanocubes to N=2 in nanoplatelets, indicating that the approximate d = 5.8 Å value often used to estimate the thickness of a single [PbBr6] 2octahedron is imprecise for thin nanostructures. Third, the superlattice periodicity fluctuation (σL) establishes a figure of merit for the superlattice structural perfection and its upper boundary can be quickly estimated from the Eq.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…crowdions-voidions pair). 37,38 Second, the sensitivity to the atomic planes periodicity d revealed an anisotropic 3.4% expansion of the CsPbBr3 structure in going from N=13 nanocubes to N=2 in nanoplatelets, indicating that the approximate d = 5.8 Å value often used to estimate the thickness of a single [PbBr6] 2octahedron is imprecise for thin nanostructures. Third, the superlattice periodicity fluctuation (σL) establishes a figure of merit for the superlattice structural perfection and its upper boundary can be quickly estimated from the Eq.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…The one exception observed was the SC phase in the Hertzian model whose vacancies were extended in two dimensions, in contrast to the one-dimensional distortions seen in the previous studies of SC crystal of repulsive particles. 5 We did, however, observe a number of other “one-dimensional” defects, including voidions in the hexagonal (H) crystal of Hertzian spheres and crowdions in BCC crystals of both models, with the concentration of the latter reaching up to 0.01 interstitials per lattice site.…”
Section: Introductionmentioning
confidence: 70%
“…However, relatively recent work on simple cubic (SC) lattices have shown that at least for some colloidal crystals, even simple point defects can extend over large areas and occur in high concentrations. [3][4][5] In particular, it was found that these SC crystals contain large numbers of vacancies, up to 0.06 per lattice site, that cause one-dimensional lattice distortions along the three main crystalline lattice directions. These one-dimensional deformations are aptly named voidions, as a counterpart to the crowdion -a largely one-dimensional lattice distortion caused by an interstitial.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike more common interstitials and vacancies, the extra or missing particle(s) is (are) not localized to a single site, but instead effectively spread out over many sites with fractional occupancy. Ensembles of cubes simulated with thermal agitation have been shown to display vacancy-type crowdions as an emergent behavior (48,49). This suggests that stochastic versions of cube-type lattice robots might display crowdion-type mass transport without careful algorithmic control of neighbor bonding and only mild module compressibility.…”
Section: Vansaders and Glotzermentioning
confidence: 99%